THE MANAGEMENT SYSTEM IMPROVEMENT AND REPAIR COMPANY BASED IMPLEMENTATION OF MS ISO 9000 - Chaikovska, E. O. (Science and Transport Progress, 2006)
Experience of perfection of the control system by a repair enterprise on the basis of introduction of the ISO 9000. standards is described in the article.